Beyond willpower : the secret principle to achieving success in life, love, and happiness - Loyd, Alex (Harmony Books, 2015)
"Did you know that most self-help programs that follow the standard success blueprint have a 97% failure rate? The truth is that the typical personal improvement mantra of tapping into your willpower and activating the power of positive thinking is actually a recipe for failure. In Beyond Willpower, bestselling author and psychological counselor Alexander Loyd, PhD, ND, reveals a unique, highly effective program to help you finally achieve the life you want and the success you deserve. Science has proven that stress, or internal fear, is the primary source of virtually any problem we encounter- physical, spiritual, emotional, and even circumstantial. New research has shown that fear is literally programmed into us at the cellular level, which is why most of us are unable to turn off our stress response by willpower alone. For the first time, this book teaches you how to change your cellular programming from fear to love, triggering a natural chemical chain reaction that fuels you for your best success. Rooted in science, ancient wisdom, and proven therapeutic techniques to remove personal obstacles that sabotage us, Beyond Willpower offers a revolutionary 40-day holistic program based on more than 25 years of clinical experience. With this program you will identify and clarify what fundamentally defines success for you. Then you'll receive the three simple tools you need to internally shift from fear to love physically (using the Energy Medicine tool), mentally (using the Reprogramming Statements tool), and spiritually (using the Heart Screen tool). You'll also have free access to the unprecedented "Success Issues Finder" test, which accurately diagnoses your unconscious and subconscious issues related to success and failure, happiness and unhappiness. No matter how you define success - as wealth, career satisfaction, healing of health issues, or resolution of relationship problems -Beyond Willpower will help you achieve it once and for all, quickly and for the long term"--